Multicultural Learning Management in Elementary Schools (Case Study of Brawijaya Smart School) - Ade Bagus Permana Putra; Burhanuddin; Raden Bambang Sumarsono; Yusi Putri Lailatul Musyarofah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The principal plays a crucial role in achieving the school's objectives and ensuring smooth operations. Effective school management is influenced by organizational culture and leadership style, which directly impacts the school's performance and condition. Quality schools typically have a positive culture, harmonious relationships between quality and management, and routinely collect and analyze data for planning and development. In the context of multicultural education, management involves developing policies, curriculum, teaching methods, and evaluations that reflect students' cultural backgrounds, aiming to create an inclusive and fair learning environment. At SD Brawijaya Smart School, the implementation of multicultural learning management is vital due to the cultural diversity of students, reflecting the pluralism of Malang city. This process includes planning, implementation, and evaluation that are responsive to students' cultural needs and actively involve the school community. This research uses a qualitative approach with techniques such as interviews, observations, and documentation studies, involving the principal, curriculum vice principal, teachers, and parents as participants. The findings indicate that SD Brawijaya Smart School integrates multicultural education through annual and semester programs tailored to cultural diversity, along with teacher training. Evaluation is conducted informally through observations and formally through tests to assess students' understanding and attitudes towards cultural diversity. Through interactive teaching methods and varied assessments, the school strives to create an inclusive learning environment that supports students' academic and social development while integrating values of respect and understanding of cultural differences.